Protecting Your Pet from Pesticides - Frederick M. Fishel (EDIS, 2005)
This guide explains precautionary measures that can be used to protect pets from injury due to pesticides used in and around the home. This document is PI-81, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date October 2005.